Morphological variability of Alveolophora jouseana (Bacillariophyta) from type material - Usoltseva, Marina V. (Phytotaxa, 2022)
A morphological variability study was carried out on the type material of Alveolophora jouseana using light and scanning electron microscopy. The new observations allowed us to extend diagnostic descriptions for the ultrastructure of this taxon, as well as its biometrics regarding diameter, number of areolar rows in 10 μm, and number of costae in 10 µm. Alveolophora jouseana shows a close similarity to A. baicalensis, another species of the same genus with which it co-occurs.